The LP-MOCVD of CdS/Bi2S3 bilayers using single-molecule precursors - Monteiro, OC (2004)
The single-molecule precursors [Cd(S2CNMe n-Hex)2] and [Bi(S2CNMe n-Hex)3] (Me = methyl; n-Hex = n-hexyl) were used to prepare CdS/Bi2S3 layers by low-pressure metal organic chemical vapour deposition (LP-MOCVD). The bilayers were deposited onto glass substrates at 400–450 jC for varying growth conditions. The materials were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and optical measurements. The results were compared with those obtained for the single phases.